Students’ Perception about Teachers’ Class Room behavior at secondary Level - Sumaira Bibi,; Wajid Mahnaz,; Naseem Akhter,; Javeria Arshad Kiani,; Attia Manzoor, (Al-Qanṭara, 2023)
Teacher behaviour encompasses the ways in which teachers communicate and engage with their students, as well as their ability to create a positive and supportive learning environment. At the secondary level, teachers play a critical role in shaping students' behaviour and academic performance. This study investigated the perceptions of secondary school students regarding their teachers' classroom behaviors and their satisfaction levels with these behaviors. The study employed a descriptive survey design, with a sample size 325 students from 22 public secondary schools in Tehsil Kallar Syedan, District Rawalpindi, Pakistan. Data was collected using a questionnaire with a Likert scale, and statistical techniques were employed for data analysis. The findings revealed that students perceive their teachers as supportive, caring, and effective in the classroom. Teacher support and feedback were found to enhance student academic performance and engagement. Additionally, using examples for easy understanding was positively perceived by students, although some preferred alternative teaching strategies. Student satisfaction with teacher behavior was generally high. Effective classroom management, clear communication, and supportive teacher behaviors were positively associated with student satisfaction. Students agreed or strongly agreed that their teachers effectively managed the classroom and maintained discipline. Based on the study findings, it is suggested that teachers should be encouraged to develop effective communication skills, promote a positive learning environment, provide regular feedback and support, use a variety of teaching strategies, and incorporate student perspectives into teaching practices.